(untitled) (Research, Society and Development, 2022)
Syphilis is a chronic, curable and exclusive human infectious disease caused by the bacterium Treponema pallidum. This disease is sexually transmitted (acquired syphilis), or congenital. The genitals are responsible for most transmissions. Syphilis can also affect the oral cavity. The objective of this study was to carry out a bibliographical review in the databases, with the intention of describing the main characteristics of the oral manifestations caused by syphilis. The present study was prepared from a literature review in the Pubmed, Scielo and BVS databases, by scientific articles described in Portuguese and English in the period between 2017 and 2022. A sexually transmitted infection, transmitted in different ways, without the Proper care can lead to death. The clinical aspects of the lesions are heterogeneous, and may differ from other diseases including lichen planus, herpetic infections and traumatic ulcers. Because there are several differentials of syphilis, the dentist has an important role in the diagnosis.